The pre-andean roots of the north patagonian andes: early paleozoic low pressure - high temperature metamorphism of the colohuincul complex, Argentina. - Serra Varela, Samanta (2016)
Fil: Serra Varela, Samanta. Instituto de Investigación en Paleobiología y Geología, Universidad Nacional de Río Negro. Río Negro, Argentina.